Propagation Characteristics and Availability Performance Assessment for Simulated Terrestrial Hybrid 850 nm/58 GHz System - V. Kvicera; M. Grabner; O. Fiser (Radioengineering, 2010)
Results of a propagation study on a free space optical link at 850 nm on a path 853 meters long and on a parallel 58 GHz radio link obtained over a 3-year period of observation are presented. The cumulative distributions of attenuation due to all of the hydrometeors combined as well as due to individual hydrometeors were obtained for both paths. The availability performances of the FSO link, the RF link and the simulated hybrid FSO/RF system were assessed. Significantly higher availability performance was achieved for the simulated hybrid FSO/RF system than for the FSO link alone. The diversity improvement factor reached significant values for attenuation greater than 5 dB and a significant diversity gain was obtained for the percentages of time smaller than 2%.